Computer aided design of fluid power systems - Gavrilidis, Can. (Thesis (M.S.)- Bogazici University. Institute for Graduate Studies in Science and Engineering, 1986., 1986)
This project aims to an integrated computer approach for the design and simulation of hydraulic systems, using components available in market. An interactive computer software is developed, which draws a graphical layout, selects components and performs steady-state and dynamic calculations on the systems, depending on user-defined inputs, meanwhile allowing redesign or improvement of the system. The final outputs from printer and plotter can directly be taken to the construction stage, therefore cutting the need for circuit building and testing, decreasing time and money spent during design procedure of hydraulic systems. The criteria for design, graphics software, development of system dynamic models and mathematical solution methods are explained with an accuracy analysis. A users manual is developed to answer any questions that may arise to an inexperienced user.
Keywords: Fluid power technology.; Hydraulic structures.; Computer aided design.